Sosialisasi Literasi Anti Korupsi di SMA Negeri 5 Pekanbaru - Nur Azkiya Azali; Zahratul Aini; Putri Anggun Sari; M. Irfan Wahyudi; Raisya Fitria Zahra; Chandra Halim (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The anti-corruption literacy socialization held by Muhammadiyah University of Riau (UMRI) students at SMA Negeri 5 Pekanbaru is a form of community service which aims to instill integrity and anti-corruption values in the younger generation. This activity was carried out in response to the big challenge in eradicating corruption which requires awareness and active participation from all levels of society, including students. Through seminars, discussions and campaigns involving various media, UMRI students strive to provide an understanding of the negative impacts of corruption and educate students about the importance of transparency and accountability. The results of this service show that the outreach activities succeeded in building students' critical awareness of their role in eradicating corruption and strengthening their commitment to maintaining integrity in everyday life. Thus, this service makes an important contribution in creating a young generation who is ready to become agents of change in fighting corruption in Indonesia.